2018
DOI: 10.3389/fphar.2017.01000
|View full text |Cite
|
Sign up to set email alerts
|

Menthol and Menthone Associated with Acetylsalicylic Acid and Their Relation to the Hepatic Fibrosis in Schistosoma mansoni Infected Mice

Abstract: Schistosomiasis is an important parasitic disease caused by Schistosoma mansoni, an intravascular trematode. Schistosomiasis treatment is limited to just one drug, Praziquantel (PZQ). Thus, studies on new antischistosomal compounds are of fundamental importance to disease control. Here we report on the effects of Mentha piperita L. compounds – menthol and menthone – in association with acetylsalicylic acid (ASA) in the regulation of hepatic fibrosis caused by schistosomiasis granulomas. Six different groups of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…Schistosoma mansoni is a trematode that causes gastro-intestinal schistosomiasis, which is endemic in Africa, the Arabian peninsula and South America [ 123 ]. Feitosa et al found that in mice models, ASA administered with menthol and menthone act in the modulation of the inflammatory process during disease (granulomas) and might help during hepatic inflammation and fibrosis control [ 124 ].…”
Section: Resultsmentioning
confidence: 99%
“…Schistosoma mansoni is a trematode that causes gastro-intestinal schistosomiasis, which is endemic in Africa, the Arabian peninsula and South America [ 123 ]. Feitosa et al found that in mice models, ASA administered with menthol and menthone act in the modulation of the inflammatory process during disease (granulomas) and might help during hepatic inflammation and fibrosis control [ 124 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mice livers were analyzed through histology using HE staining to assess the presence and quantification of granulomas ( 24 ) and the appearance of cell infiltrate, and Masson trichrome (MT) to assess the collagen deposit ( Figure 6 ). The animals in the CTRL group had well-structured and preserved liver tissue ( Figure 6A ).…”
Section: Resultsmentioning
confidence: 99%
“…Mice livers were analyzed through histology using HE staining to assess the presence and quantification of granulomas (24) FIGURE 1 | Experimental design for immunization of the animals with the recombinant proteins NDPK and ADSL.…”
Section: Histopathology Of the Livermentioning
confidence: 99%
“…Zaia et al (2016) found that a formulation composed of menthol (30–55%) and menthone (14–32%) was able to decrease the number of Schistosoma mansoni eggs in feces, liver, and intestine of infected mice but also reduced the number of hepatic granulomas; a reduction of eosinophilia in blood and a decrease of IL-4 and IL-10 levels in the blood after treatment were also observed [ 10 ]. Subsequently, Feitosa et al (2018) found that a combination of menthol and menthone associated with acetylsalicylic acid reduces the hepatic inflammation and fibrosis in the murine schistosomiasis model [ 11 ]. Furthermore, Mohammad et al (2020) reported that the M. pulegium L. extract composed of menthol (99.23%) and limonene (0.227%) has low cytotoxicity and high activity against the Toxoplasma gondii [ 12 ].…”
Section: Introductionmentioning
confidence: 99%